Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 186750 by pascal889 last updated on 09/Feb/23

Answered by Frix last updated on 09/Feb/23

((1+(x−(1/2))^4 +(x+(1/2))^4 )/(1+(x−(1/2))^2 +(x+(1/2))^2 ))=((2x^4 +3x^2 +(9/8))/(2x^2 +(3/2)))=  =(((x^2 +(3/4))^2 )/((x^2 +(3/4))))=x^2 +(3/4)  x=2009.5 ⇒ answer is 4038091

1+(x12)4+(x+12)41+(x12)2+(x+12)2=2x4+3x2+982x2+32==(x2+34)2(x2+34)=x2+34x=2009.5answeris4038091

Terms of Service

Privacy Policy

Contact: info@tinkutara.com